ANALYSIS SYSTEM THIS STUDY AIMS TO DETERMINE THE EFFECT OF IMPLEMENTING A DATA PROCESSING SYSTEM WITH THE LEVEL OF ACCURACY OF DATA AND THE LATEST LEVEL OF POPULATION DATA AT THE REGENCY BPS OFFICE BARRU - A.Aminah; Jumria Jumria (Sean Institute, 2023)
Sources of data obtained by means of questionnaires and observations. Data analysis using linear regression formula with SPSS. The results showed that the implementation of the system data processing at the Barru Regency BPS office has been going well, which includes data collection activities, data modification, data storage and document creation population. Analysis results. linear regression using SPSS, known: value 0.005 (0.001 <0.005), and t.hit : 3678 > 2771 t.tab or t.count more greater than t.table, so that the hypothesis (H.1) is accepted, namely the implementation of data processing population has a significant effect on the level of accuracy and up-to-date data of the population as produced by the BPS of Barru Regency. There are several factors impede the implementation of the population data processing system, among other things that stand out are: the level of human resources of the BPS staff is still low (education, training and experience as well work skills), the equipment used is still simple, and the coaching fund is still lacking in the implementation of all data management activities.m Pengolahan Data Pada Kantor Badan Pusat Statistik (BPS) Kabupaten Barru